Growth Performance and Carcass Characteristics of Broiler Chickens Fed Combined Bovine and Camel Rumen Contents - Obadire, F.O.; Oso, A.O.; Yunusa, S.; Ibiwoye, K.O.; Mustapha, Y.; Osofowora, A.O.; Ejiofor, I.; Oluwatosin O.O. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
An experiment was carried out to partially substitute graded levels of combined (bovine and camel) rumen content (CCRC) for maize and subsequently determined the effect on growth performance and carcass characteristics of the broiler chickens. One hundred and fifty (150) dayold Marshall Broiler chicks were randomly allotted to 5 dietary treatments of three replicates of 10 chicks each. The experimental diets were formulated with bovine and camel rumen content (combined rumen content (CCRC)) in the diets of broilers (ratio of 1:1) at 0, 20, 25, 30 and 35% inclusion levels respectively. Data obtained were subjected to Analyses of Variance (ANOVA) in a completely randomized design (CRD) using SAS (2009) and significant means were separated using Duncan’s Multiple Range Test of same statistical package at 5% level of probability. Feed and water were supplied ad libitum for 8 weeks. Data were generated for final body weight, total feed intake, total weight gain, feed conversion ratio and carcass traits. Results of the analysis for growth performance revealed significant (P<0.05) effect of CCRC on feed intake at the starter phase while other growth parameters were not significant. Results showed that birds fed 20% CCRC have the highest total feed intake (2865.57g) while birds fed control diet recorded the least feed intake (1844.54g). Similarly, at finisher phase all the growth performances were not significantly (P>0.05) influenced across the treatment groups. However, the carcass measurements were not significantly (P>0.05) affected by the CCRC inclusion levels. It was concluded that CCRC at 35% inclusion level could be used to substitute maize in diet of finisher broiler chickens as it compared favourably with maize with better growth performance and without any negative effect on the carcass characteristics of the broiler chickens.